4(3x+2)=-5(5x-2)+2x

Simple and best practice solution for 4(3x+2)=-5(5x-2)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+2)=-5(5x-2)+2x equation:


Simplifying
4(3x + 2) = -5(5x + -2) + 2x

Reorder the terms:
4(2 + 3x) = -5(5x + -2) + 2x
(2 * 4 + 3x * 4) = -5(5x + -2) + 2x
(8 + 12x) = -5(5x + -2) + 2x

Reorder the terms:
8 + 12x = -5(-2 + 5x) + 2x
8 + 12x = (-2 * -5 + 5x * -5) + 2x
8 + 12x = (10 + -25x) + 2x

Combine like terms: -25x + 2x = -23x
8 + 12x = 10 + -23x

Solving
8 + 12x = 10 + -23x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '23x' to each side of the equation.
8 + 12x + 23x = 10 + -23x + 23x

Combine like terms: 12x + 23x = 35x
8 + 35x = 10 + -23x + 23x

Combine like terms: -23x + 23x = 0
8 + 35x = 10 + 0
8 + 35x = 10

Add '-8' to each side of the equation.
8 + -8 + 35x = 10 + -8

Combine like terms: 8 + -8 = 0
0 + 35x = 10 + -8
35x = 10 + -8

Combine like terms: 10 + -8 = 2
35x = 2

Divide each side by '35'.
x = 0.05714285714

Simplifying
x = 0.05714285714

See similar equations:

| 20x+5=24-12x | | Y=log(-3x) | | 2x+3x+5x=y | | 5x+4=x+4(2+x) | | 60x+45=285 | | 3x+17=9-5x | | 9/25-y=-1/4 | | 8x-(2x-9)=4x-(8+4x) | | y-4-7y-3= | | .69x+19=43 | | y/4=5/13 | | 675x+125=3175 | | 3y^3-2y=x-3 | | 55x+850=123 | | y-1=2/3(x=9) | | x*10+12*8=196 | | 10=y+z | | x/2-=1 | | u/10=13/11 | | 5(2x+1)=-2(3x-5) | | 6y+9-5y=-3 | | b-11.33=3.833 | | x+2.4=6.8 | | (3x+2)+58=90 | | y=2.7x+10 | | 7(d-4)+3= | | x-2+37=4x | | 2.2+x=3.5 | | (2x-1)(3-x)=6 | | 20x^2-7x=3 | | 34-171/2y=-8 | | 7z-3(4-z)=5(2z)+12 |

Equations solver categories